Hotel Development Tendencies in the Russian Federation - Yurievna Nikolskaya, Elena; Alekseevich Popov, Leonid; Petrovich Kulgachev, Ivan; Arturovna Blinova, Ekaterina; Venerovich Arifullin, Marat (Opción, 2019)
The article is dedicated to the analysis of development tendencies in the hotel business in the Russian Federation. It has been estab-lished that the current national operators should create hotel chains with a universal set of services and high-quality service. They can do this by purchasing and renovating currently available low- and mid-level hotels and by increasing their star ratings. The estab-lishment of such chains in the market can bring advantages via market dominance. It has been proved that for the expansion of the hotel business, it is essential to create a favorable investment climate at the macro level, which includes attractive and predicta-ble economic con- ditions in the country, and at the micro level, comprising fiscal, customs and other benefits for enterprises that specialize in hotel services for the purpose of drawing domestic and foreign capital.